The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1080/10400435.2015.1059384
|View full text |Cite
|
Sign up to set email alerts
|

Technology delivered self-monitoring application to promote successful inclusion of an elementary student with autism

Abstract: The ever-increasing prevalence of children diagnosed with autism spectrum disorder (ASD) is paralleled in public educational settings, including general education classrooms. Challenges with social/behavioral functioning, including limited self-management and behavior inhibition, can lead to off-task and disruptive behaviors that interfere with acquisition of academic and social skills. Without effective and efficient interventions, opportunities to participate in inclusive settings will likely be reduced. Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 23 publications
(25 reference statements)
0
22
0
1
Order By: Relevance
“…Intervals were set at 30-s intervals for all four participants. This decision was based on previous research utilizing the device (e.g., Crutchfield et al, 2015, Rosenbloom et al, 2016, Wills & Mason, 2014 that demonstrated that 30 s was an appropriate interval length to use initially. Participants were asked during their training session if they would prefer a flashing screen or noise notification option.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Intervals were set at 30-s intervals for all four participants. This decision was based on previous research utilizing the device (e.g., Crutchfield et al, 2015, Rosenbloom et al, 2016, Wills & Mason, 2014 that demonstrated that 30 s was an appropriate interval length to use initially. Participants were asked during their training session if they would prefer a flashing screen or noise notification option.…”
Section: Methodsmentioning
confidence: 99%
“…The I-Connect Self-Monitoring (SM) intervention is one such technology-delivered application that is a single component system (i.e., a tablet) to deliver interval self-monitoring prompts and record data. The I-Connect SM intervention has increasing empirical support as an effective self-monitoring intervention (Clemons et al, 2016, Crutchfield et al, 2015Rosenbloom et al, 2016;Wills & Mason, 2014). Wills and Mason (2014) developed the I-Connect SM intervention to provide a non-obtrusive, self-monitoring delivery format.…”
Section: I-connect Self-monitoring Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual aids (e.g., [279]), on the other hand, allow carers to communicate tasks and events in the near future in a structured way to autistic children. Technologies aiming at general social communication are used to guide the children in behaviour that is deemed socially appropriate (e.g., [278]), to understand more about the current social-emotional context as established by others and one self (e.g., [211]) or prompt them to initiate social interaction, for example, through vocalisations (e.g., [118]). Finally, the application providing portable medical information to autistic children [136] can communicate certain needs to those assisting in crisis situations, where a child might not be able to express them otherwise.…”
Section: Assistive Technologymentioning
confidence: 99%